2017
DOI: 10.1021/acscatal.7b01696
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Enhanced Accessibility of Acid Sites in Micromesoporous Mordenite Zeolites on Hydroisomerization of n-Hexane

Abstract: This paper describes a study of the nature and the accessibility of the acid sites in micromesoporous mordenite zeolites obtained by desilication and dealumination and analysis of their activity and selectivity in the hydroisomerization of n-hexane. Alkaline−acid, acid−alkaline−acid, and fluorination−alkaline−acid postsynthesis treatments were employed for the preparation of micromesoporous mordenites. The FTIR spectra of adsorbed d 3 -acetonitrille, 27 Al MAS NMR, HR-TEM, and N 2 adsorption were used for quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 68 publications
5
69
0
Order By: Relevance
“…Taking into account that acid sites located in the 8MR side‐pockets are not accessible to alkanes, the improved catalytic behavior of MOR‐0.25 can be explained by a decreased amount of BAS in the main 12MR channels, where the hydroconversion reaction of alkenes takes place. The lower accessible acidity of Pd/MOR‐0.25 shifts the hydrogenation/acidity balance towards ideal hydrocracking behavior.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account that acid sites located in the 8MR side‐pockets are not accessible to alkanes, the improved catalytic behavior of MOR‐0.25 can be explained by a decreased amount of BAS in the main 12MR channels, where the hydroconversion reaction of alkenes takes place. The lower accessible acidity of Pd/MOR‐0.25 shifts the hydrogenation/acidity balance towards ideal hydrocracking behavior.…”
Section: Resultsmentioning
confidence: 99%
“…The introduction of a second level of intracrystalline porosity to the MOR pore system would be advantageous to the many acid‐catalyzed hydrocarbon conversion reactions that involve large paraffinic and aromatic molecules. A general “top‐down” approach to prepare mesoporous mordenite zeolites via desilication, dealumination or a combination of these approaches has been extensively examined. Even though these techniques are commercially available and can be scaled up, there is little control over the textural and acidic properties of the final materials.…”
Section: Introductionmentioning
confidence: 99%
“…Isomerization of normal hexane (n-C 6 ) has been recognized to be one of the most economical units to boost octane level especially for the lower boiling gasoline. The process is typically catalyzed by bifunctional Pt/H-mordenite catalysts [2]. Recently, zirconia has been reported as a popular support for various reactions because of its high thermal stability, acid-base properties, and redox surface properties.…”
Section: Introductionmentioning
confidence: 99%
“…Pastvova et al have reported that the controlled alkaline-based treatments of the MOR framework lead to the better preservation of acid sites and the formation of well-developed secondary mesoporosity. The existence of mesopores structure results in high yields of branched isomers and limits nonselective subsequent cracking reactions [22]. Zhang et al found that the formation of mesopores for hierarchical porous MOR used as the supports could be beneficial to the dispersion of Pt species which can improve the contact of the reactants to the active sites.…”
Section: Introductionmentioning
confidence: 99%